1990
DOI: 10.1111/j.1365-2621.1990.tb03910.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trimming and Added Connective Tissue on Compositional, Physical and Sensory Properties of Restructured, Pre‐cooked Beef Roasts

Abstract: Restructured beef roasts were prepared using trimmed (intermediate or extensive) and chunked (kidney plate or hand knife) beef shoulder clods with varying levels (0, 10, 20 or 30%) of added connective tissue (flaked with ComitrolR). Intact beef top rounds (control) and all restructured roasts were water cooked to 62.8"C internal temperature. Increasing connective tissue increased (PcO.05) tenderness and fat of restructured products with no dcletcrious effect (P >O.OS) on product bind. Addition of 30% connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…There were no differences (P>O.O5) in moisture content between the control and either IOPHCT or lOCT, suggesting that differences in juiciness were not due to moisture content but to a greater ability of added connective tissue to bind water. This observation was in agreement with Liu et al (1990), who found a decrease in juiciness when 30% connective tissue was added back to extensively trimmed muscles. Although not significant (P>O.O5), 10% additions of Cl' (P<O.O9) and PHCT (PcO.08) tended to decrease beefiness scores.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…There were no differences (P>O.O5) in moisture content between the control and either IOPHCT or lOCT, suggesting that differences in juiciness were not due to moisture content but to a greater ability of added connective tissue to bind water. This observation was in agreement with Liu et al (1990), who found a decrease in juiciness when 30% connective tissue was added back to extensively trimmed muscles. Although not significant (P>O.O5), 10% additions of Cl' (P<O.O9) and PHCT (PcO.08) tended to decrease beefiness scores.…”
Section: Resultssupporting
confidence: 92%
“…Instron evaluations indicated that l.OG, 5CT, lOCT, and 10 PHCT, treatments had greater (PcO.05) tensile strength than the control and SPHCT treatments (Table 1). When compared to the control, the most dramatic increase in tensile strength occurred for products containing either 10% preheated or 10% raw CT. Liu et al (1990) did not find a significant increase in tensile strength as added connective tissue increased to 30%. Their observation may have been due partly to the increase in fat content from 4.48 to 7.76% as connective tissue increased from 10 to 30% (Liu et al, 1990).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…However, determining the precise mechanism of its influence on texture is complex. Liu et al (1990) found that particle size did not affect (p>0.05) the collagen content of restructure roasts.…”
Section: Protein Extractabilitymentioning
confidence: 92%
“…Boles and Shand (1998) found that neither method of size reduction nor size of opening affected the cook yield of restructured beef steaks. Addition of various proportion of connective tissues significantly (p<0.05) reduced the cooking yield of restructured beef steaks (Liu et al, 1990). Cook yield of restructured mutton steaks was significantly (p<0.05) affected by meat particle size and 20 mm particle size has more cook yield than 12, 8 and 5 mm particle size (Sen and Karim, 2003).…”
Section: Quality Of Restrucutred Meat Products Cooking Yieldmentioning
confidence: 99%